Interprofessional Education and its Effect on Team Performance in Anesthesia, Nursing, Anesthetic Technology, and Social Work: A Systematic Review - Najlah, Omnyia Omar Abu; Suwaydi, Ali Ahmed; Alfarsi, Mohammed Barakah; Almutairi, Mohammed Fahad Muzn; Alsulami, Enad Aateq; Alzahrani, Thamer Mohammed; Fallatha, Fatimah Omer; Alsharif, Najat Onaitallah; Aldosari, Bashair Abdullah; Al-Harbi, Ahmed Hamdan (Journal of Ecohumanism, 2024)
Background: Interprofessional education (IPE) has emerged as a cornerstone of modern healthcare training, emphasizing collaboration among diverse disciplines to improve patient outcomes and professional competence. In high-stakes clinical environments such as anesthesia, nursing, anesthetic technology, and social work, where teamwork and communication are critical, IPE can enhance coordination, safety, and decision-making. Objective: This systematic review aimed to evaluate the impact of interprofessional education on team performance, communication efficiency, and collaborative practice among anesthesia providers, nurses, anesthetic technologists, and social workers. Methods: A systematic search was conducted across PubMed, Scopus, CINAHL, and Web of Science databases for studies published between 2010 and 2025. Eligible studies included quantitative, qualitative, and mixed-methods designs that investigated IPE interventions involving at least two of the mentioned professions. Data were extracted on educational format, duration, assessment tools, and outcomes related to teamwork, communication, and clinical performance. Results: Twenty-six studies met inclusion criteria. Across all studies, IPE significantly improved interprofessional communication, situational awareness, and collaborative decision-making. Simulation-based IPE, in particular, enhanced crisis management and intraoperative teamwork in anesthesia settings. Nursing and anesthetic technology participants reported increased role clarity and confidence in shared responsibilities, while the inclusion of social workers improved holistic patient care planning and psychosocial support. Quantitative analyses showed consistent increases in teamwork scores (average 20–35% improvement post-intervention) and self-efficacy ratings. Conclusion: Interprofessional education positively influences team performance in perioperative and psychosocial care contexts by fostering mutual respect, role understanding, and coordinated clinical decision-making. Integrating structured IPE modules into anesthesia, nursing, and allied health curricula is essential to strengthen collaborative competencies and optimize patient safety. Future research should employ standardized assessment tools and long-term follow-up to determine the sustainability of these improvements.